EARLY AMBULATION TO REDUCE RISK OF COMPLICATIONS AFTER TOTAL KNEE REPLACEMENT: DOI: https://doi.org/10.35654/ijnhs.v2i2.87 - Juliana Gracia Massie; Tuti Herawati (Alta Dharma Publisher, 2019)
Osteoarthritis is one of the degenerative health problems in the urban areas that attack many elderly people. One of the treatments of osteoarthritis is surgery to replace the damaged joint. The phenomenon occurred on many patients after the surgery for joint replacement is the lack of knowledge of the patients about the importance of early post-surgical ambulation. This paper is a case study with the aim of analyzing the benefits of early ambulation on the patients after total knee replacement at one of the Public Hospitals in Jakarta. Educating patients in the pre-operative stage of early ambulation is proven to be effective in reducing postoperative complications. Keywords: early ambulation, osteoarthtritis,total knee replacement.